Influence of geographical locations on yield, oil productivity and fatty acid profiling in four olive cultivars - Iqbal, Muhammad Azhar; Feroze, Muhammad Aqeel; Azam, Muhammad; Asif, Muhammad; Umer, Muhammad Ali; Khan, Muhammad Arslan; Ali, Hina; Lyu, Qiang; Haider, Sakeen-Tul-Ain; Liaquat, Mehwish; Yasmin, Zarina; Answer, Muhammad Ramzan; et al. (Emirates Journal of Food and Agriculture, 2023)
Olives and its oil are considered an imperative element of diet due to their excellent nutritional quality. Geographical factors (i.e., geology, slope, elevation and temperature) and genetic variability in different olive cultivars influence plant growth, yield, oil and profiling of fatty acids. The prime objective of this investigation was to demonstrate the prodigious consequences of high temperature on the growth, production, and fatty acid composition of four olive cultivars (Coratina, Frantoio, Ottobratica and Leccino) at three different geographical locations (BARI, IOF, HRS) with the range of 460-751 m altitude during the year 2017 and 2018. The study has been carried out to investigate different parameters such as climatic conditions (rainfall and temperature), phenological attribute and yield traits (fruit set, fruit weight, yield, and oil content), and oil quality and profiling of fatty acids (free fatty acid contents, peroxide, palmitic acid, palmitoleic acid, oleic acid, linoleic acid, and linolenic acid). The results indicated a positive correlation of yield with rainfall and negative with the temperature was observed among olive cultivars. The results showed higher rainfall (1189 mm) and temperature (37.51 °C) at location-1 and lower rainfall (525 mm) and temperature (36.05 °C) at location-3. Coratina and Frantoio depicted significantly higher fruit set and yield in warmer climatic regions (Location-1 and Location-2) while Leccino and Ottobratica showed better results in the cooler region. Higher oil content was found in Frantoio and Coratina at location-3 among other locations and other cultivars. Overall, the lowest free fatty acid value was exhibited in Coratina and the highest in Ottobratica at all locations in both seasons. The contents of peroxide were observed higher in Leccino and lower in Coratina at all locations. The results revealed less variation among fatty acid composition in cultivars and seasons, however, palmitic acid, palmitoleic acid and oleic acid contents were found higher at location-2, linoleic acid at location-3, and linolenic acid at location-2 in all four olive cultivars. Custer analysis revealed two main groups and group-I contained two subgroups (A and B) while group-II contained three subgroups (C, D and E). In principal component analysis (PCA), PC1 axis had Leccino-L3, Leccino-L1, Frantoio-L1, Ottobratica-L1, Coratina-L1, and Leccino-L3 and explained 91.99% of the total variation. Therefore, geographic location influence growth, yield and olive oil quality attributes. Keywords: Climatic conditions; Acid value; High temperature; Free fatty acids;· Oleic acid;· Olive cultivars; Pothwar-Pakistan